Nutritional Assessment and Comparison between Brown and Milled Rice Landraces (Anadi, Bhotange, and Kalo Nuniya) of Nepal - Rai, Sakul; Khadka, Dambar Bahadur; Pokharel, Bimala (Tribhuvan University Journal of Food Science and Technology, 2023)
The main objective of this study was to assess and compare the nutritional quality of brown- and milled rice landraces (Kalo Nuniya, Anadi, and Bhotange) of Koshi Province. Paddy samples were cleaned to remove dockage and sun-dried until about 13-14% moisture to ensure maximum hulling- and milling recovery. Paddy samples were shelled and milled to obtain brown (unpolished) rice and milled (white or polished) rice, respectively and were stored in double-sealed re-closable low-density polyethylene (LDPE) zipper bags (62.5 µm) at ambient temperature (23-27°C) until analysis. As expected, brown rices had better nutritional profiles than their milled counterparts with significantly higher (p<0.05) crude fat (2.99± 0.10 − 3.99 ± 0.09%), crude fiber (0.12 ± 0.00 − 0.70 ± 0.02%), and total ash (1.53 ± 0.2 − 3.71 ± 0.30%) content. Among the brown rices, Anadi brown had better nutritional profile with the highest iron (1.56 ± 0.14 mg/ 100 g), calcium (86.4 ± 3.30 mg/100 g), total ash (3.71 ± 0.30%), crude fiber (0.70 ± 0.02%), and crude fat content (3.99 ± 0.09%). Bhotange and Kalo Nuniya had uniform distribution of iron and calcium, respectively, throughout the entire rice kernel.